The Effect of Laser Power and Laser Scan Passes on Bending Angle of Stainless Steel AISI 304 Laser Bending - N., Affaf; H.S., Wong; M. H., Aiman; M., Ishak; M. M., Quazi (Springer, 2022)
The application of laser bending of thin sheet metal are quite limited given that this forming process is widely used in various industries. The aim of this paper is to study the effect of laser power and laser scan passes on bending angle of stainless steel AISI 304 lasers bending. This study considers using parametric combinations of laser power and laser scan passes (number of loops) as the laser bending process parameters. The corresponding effects of these process parameters on bending angle of stainless-steel thin sheet metal (t = 0.1 mm) was observed. The results obtained shows that the bending angle increased with increased in laser power and laser scan passes, meaning that these parameters does significantly affect the bending angle. Other than bending angle, there were also a few bulges observed at certain location along the laser scan path for certain parametric combination of process parameters tested.